2017
DOI: 10.1097/ccm.0000000000002363
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Is Required for Local and Remote Ischemic Preconditioning in Multiple Organ Protection Against Sepsis*

Abstract: MicroRNA-21 is required for local and remote ischemic preconditioning in multiple organ protection against sepsis, and up-regulation of miR-21 may be a potential therapy for sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 42 publications
5
80
0
Order By: Relevance
“…MicroRNAs are an important player in this process. For example, miR-21-5p is required for local and remote ischemic preconditioning in multiple organ protection against sepsis, and an up-regulation of miR-21-5p may be a potential therapy for sepsis [55]. Some studies show that miR-125a-5p prompted the activation and proliferation of hepatic stellate cell by partially down-regulating FIH1 in liver fibrosis [15], and miR-133a-5p was protective against hypoxia/reoxygenation (H/R) injury in vitro by targeting MAPK6 in hepatocytes [56].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are an important player in this process. For example, miR-21-5p is required for local and remote ischemic preconditioning in multiple organ protection against sepsis, and an up-regulation of miR-21-5p may be a potential therapy for sepsis [55]. Some studies show that miR-125a-5p prompted the activation and proliferation of hepatic stellate cell by partially down-regulating FIH1 in liver fibrosis [15], and miR-133a-5p was protective against hypoxia/reoxygenation (H/R) injury in vitro by targeting MAPK6 in hepatocytes [56].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that brief ischemia and reperfusion in kidney can provide protection against organ injury at local and remote sites [22]. Many other observations have also suggested that the preconditioning effect is systemically mediated [23, 24].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous observations indicated that the beneficial effect of renal IPC not only provides local protection but also protects remote organs, suggesting that the preconditioning effect might also be systemically mediated [22]. Another study reported that circulating immune cells responding to an initial ischemic event could mediate decreased tissue injury after a second ischemic event [57].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-21 is one of the most highly upregulated miRNAs during kidney injury, both acute kidney injury [22] and CKD [17]. In our previous study, we revealed that miR-21 was up-regulated soon after ischemia in a mouse model of renal ischemia reperfusion injury [23]. Moreover, when renal tubulointerstitial fibrosis appears, miR-21 expression is maintained at a high level.…”
Section: Introductionmentioning
confidence: 99%